Fluorometric Method for Microdetermination of Human Serum Albumin Using Substituted 3H-Indole Compound - Xu, Tongkuan; Qu, Fengzuo; Han, Pengfei; Wang, Zhaowen; Cui, Li (Asian Journal of Chemistry, 2014)
A simple, sensitive and reproducible fluorometric method for determining nanoamount of protein is developed. The method is based on the reaction between protein and 3H-indole compounds in aqueous solution. Under the optimized experimental conditions, there is little interference with amino acids and most metal ions. In the detection of total amount of proteins in human serum albumin, the values obtained by this method are close to those of the BCG method. The binding reaction mechanism between this compound and human serum albumin in aqueous solution was studied using fluorescence. Their binding constant is Ka = 8.51 × 105 L mol-1 and the binding site number is n = 1.2. It is confirmed that the combination is a single static queching process. According to the resonance energy transfer theory, the distance between the molecule and tryptophan of human serum albumin is 37.3 Å and the förster energy transfer is very efficient as high as 93.7 %.